SISTEM RELIGI MASYARAKAT SUKU AKIT DI DESA SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 1995-2013 - Melinda, Dewi; Ibrahim, Bedriati; Saiman, Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: Riau Province is a central for culture and tradition of proto malayan. This assumption is supported by the fact that there are a number of tribes â€œKomunitas Adat Tertinggal (KAT)â€, such as suku Laut or Suku Akit is still living in Riau. This research aims to reveal the system of religion of community suku akit in the Selat baru village, subdistrict Bantan, district Bengkalis in 1995-2013.The method used in this research is descriptive method. The result of this research is revealed that the system of religion of suku Akit has embraced the religion of islam, Christians and Buddhism, However they still carry the tradition of ancestor animism. In addition The community of suku Akit is a plurality society, this is evident by celebrating religious holidays together. it is due to the reason that they came from ancestors who have the same beliefs that animism. Beside that, celebrating religious holidays together will create the harmony between community. In community suku akit, circumcised ceremony is a tradition that sould be done on adolescent 7 untill 12 years old.Keywords : Sytem Religious, Community, Suku Akit